Perceptions of parents of pediatric patients with acute lymphoblastic leukemia on oral chemotherapy administration: A qualitative analysis. Issue 1 (7th September 2021) - Tang, Natalie; Kovacevic, Anja; Zupanec, Sue; Sivananthan, Araby; Patel, Rikesh; Patel, Priya; Vennettilli, Ashlee; Paw Cho Sing, Edric; Alexander, Sarah; Sung, Lillian; Dupuis, L. Lee
Abstract: Objective: To describe the experiences and perspectives of parents of pediatric patients with acute lymphoblastic leukemia (ALL) regarding oral chemotherapy administration during maintenance therapy. Methods: English‐speaking parents of patients 4 to <18 years who were receiving ALL maintenance oral chemotherapy were eligible to participate in this mixed methods study. Using semi‐structured interviews, we asked participants how difficult they found oral chemotherapy administration. We also probed regarding barriers and facilitators of oral chemotherapy administration and strategies used to overcome challenges. Lastly, we asked participants for their advice to future parents giving oral chemotherapy to their children. Results: Twenty‐three participants were interviewed. One‐fifth of participants stated that oral chemotherapy administration at home was hard or very hard. Common factors influencing oral chemotherapy administration were product‐related (e.g., formulation) and treatment‐related adverse effects (e.g., nausea), lifestyle adjustment (e.g., fitting in with family schedule), and attitudes (e.g., onus of medication administration). Strategies to address oral chemotherapy administration included several administration techniques, scheduling of medication administration, and normalization of medication taking. Conclusions: Oral chemotherapy administration during ALL maintenance therapy was hard for some parents. Identification of these parents and discussion of strategies to facilitate adherence to oral chemotherapy regimens may optimize patient outcomes.